On the trade in wool and wooolens including an exposition of the commercial situation of the British empire (s.n.], 1814)
The Pamphleteer ; vol. III, no VI,. p. 282-328. - Extracted from the reports addressed to the Wool-meetings at Lewes in the years 1809, 1810, 1811 and 1812.